2017
DOI: 10.24041/ejmr2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices of General Practitioners and Homeopaths Regarding Food Allergy and Anaphylaxis in India- A Comparitive Study

Abstract: Food allergy (FA) is a growing health problem in India and worldwide with notable prevalence in infants when compared with children and adults. Multiple genetic and nutritional factors play an important role in etiology of FA leading to morbidity and mortality. As general practitioners (GPs) and homeopaths are the first persons to be approached by patients with possible FA, the need for evaluating their Knowledge, Attitude and Practices (KAP) towards the same are essential to be studied.A total of 214 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…21 We observed that only 56% of the respondents felt confident that they could treat a case of anaphylaxis which was lower compared with a study conducted in Hyderabad among general practitioners and homeopaths, where 77.5% of subjects were confident that they could appropriately manage a case of anaphylaxis. 22 This might be due to inclusion of early career physicians, namely interns as well as nurses in our study.…”
Section: And 13 )mentioning
confidence: 99%
“…21 We observed that only 56% of the respondents felt confident that they could treat a case of anaphylaxis which was lower compared with a study conducted in Hyderabad among general practitioners and homeopaths, where 77.5% of subjects were confident that they could appropriately manage a case of anaphylaxis. 22 This might be due to inclusion of early career physicians, namely interns as well as nurses in our study.…”
Section: And 13 )mentioning
confidence: 99%